Dynamics of Contract Cancellation in Civil Law and its Relevance for Consumer Protection: Dinamika Pembatalan Kontrak dalam Hukum Perdata dan Relevansinya bagi Perlindungan Konsumen - Ratrisari, Elizabeth Prima; Rajagukguk, Jemimah Puteri; Napitu, ⁠Olivia Panjiani; Manalu , Veronica Enjelina; Ginting, Gavra Natadavie (Universitas Muhammadiyah Sidoarjo, 2025)
Background (General): Contract annulment plays a significant role in upholding legal certainty and fairness within civil law frameworks. Background (Specific): In Indonesia, the Civil Code (KUH Perdata) provides the basis for contract validity, focusing on essential elements such as consent, legal capacity, and lawful object. Knowledge Gap: However, there is limited comprehensive analysis of how principles like good faith and fairness influence contract annulment beyond formal legal criteria. Aim: This study aims to examine the legal grounds, procedures, and implications of contract cancellation in Indonesia, particularly under the Civil Code, Consumer Protection Law, and Electronic Information and Transactions Law. Results: Through normative juridical analysis and case law review, the findings reveal that annulment is influenced not only by statutory violations but also by equitable considerations, such as imbalance in bargaining power and misrepresentation. Novelty: The study highlights how Indonesian courts increasingly incorporate substantive justice and good faith into annulment decisions, marking a shift from rigid formalism. Implications: These findings offer valuable insights for legal practitioners and business actors in mitigating contractual disputes and aligning agreements with evolving judicial interpretations. Highlights: Emphasizes the role of fairness and good faith in contract annulment. Integrates statutory analysis with judicial interpretation. Highlights practical implications for legal and business practices. Keywords: Contract Annulment, Civil Law, Legal Protection.